2020
DOI: 10.3390/ijerph17082881
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyanobacterial Bloom Extracts on the Biomass, Chl-a, MC and Other Oligopeptides Contents in a Natural Planktothrix agardhii Population

Abstract: Blooms of the cyanobacterium Planktothrix agardhii are common in shallow, eutrophic freshwaters. P. agardhii may produce hepatotoxic microcystins (MCs) and many other bioactive secondary metabolites belonging mostly to non-ribosomal oligopeptides. The aim of this work was to study the effects of two extracts (Pa-A and Pa-B) of P. agardhii-predominated bloom samples with different oligopeptide profiles and high concentration of biogenic compounds on another natural P. agardhii population. We hypothesised that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Therefore, the correlations between NRPs from different classes, particularly with NODs, cannot be related to the interlinked metabolic pathways. These correlations indicate that some NRPs may have complementary functions in the cyanobacterium, as previously suggested 31 , 52 . Further studies on the mechanisms behind the synchronized dynamics of such NRPs are needed.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, the correlations between NRPs from different classes, particularly with NODs, cannot be related to the interlinked metabolic pathways. These correlations indicate that some NRPs may have complementary functions in the cyanobacterium, as previously suggested 31 , 52 . Further studies on the mechanisms behind the synchronized dynamics of such NRPs are needed.…”
Section: Discussionsupporting
confidence: 77%
“…M. aeruginosa PCC 7806 and PCC 9432) 31 , 51 . Also, Planktothrix agardhii exposed to two distinct cell extracts of bloom samples predominated by P. agardii (95% total biomass) had its NRPs levels both higher or lower than in the controls (monocultures), depending on the cell extract 52 . It is important to note that each cell extract consists of P. agardii strains of several chemotypes of different NRP profiles 52 , 53 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A high variety of the MCs and bioactive non-ribosomal peptides was detected in scum samples of P. agardhii [ 48 ]. The current experimental study demonstrated that the toxic P. agardhii strain was able to produce three different variants of the MCs, and the shift in the proportion of MCs variants under varied nutrient conditions was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In subtropical and temperate lakes, Dolichospermum and Aphanizomenon usually become dominant when the abundance of Microcystis decreases in winter and spring [ 12 , 13 , 14 ]. However, Raphidiopsis forms perennial blooms in many tropical and subtropical lakes [ 15 ], whereas Planktothrix can be exclusively dominant in temperate lakes with relatively low water temperatures [ 16 , 17 ]. Therefore, temperature is a critical factor affecting the composition of the cyanobacterial community.…”
Section: Introductionmentioning
confidence: 99%